Small-scale variability in Arctic zooplankton around Southampton Island, Nunavut - Andrea Niemi; C-Jae Breiter; Sławomir Kwaśniewski; Mateusz Ormańczyk; Alexis Burt; Jens Ehn; Elizabeth Kitching; Jessica Mai; C. J. Mundy (Polar Biology, 2026)
Polynyas, tidal straits, and variable water column structure support diverse and productive habitats around Southampton Island, northern Hudson Bay, Nunavut, Canada. This study provides the first description of zooplankton at depths between 18 and 313 m around the island, including pelagic larval stages of benthic invertebrates (i.e., meroplankton). From the stations sampled in August 2018 and 2019, 83 taxa were identified with an average station species richness of 27. Bivalve larvae were present at all stations and were the most abundant meroplankton taxa. A distinct Northern and Southern zooplankton assemblage was identified. Average total zooplankton abundance was 5.4 times higher at Northern stations in Frozen Strait, and at stations adjacent to Foxe Basin and Foxe Channel, relative to Southern stations. The Northern assemblage was numerically dominated by calanoid copepods whereas the Southern assemblage had higher abundances of cyclopoid copepods including Oithona similis . Metridia longa and Oikopleura spp. were strong indicator taxa of the Northern assemblage, in contrast to hydrozoans (i.e., Aglantha digitale and Aeginopsis laurentii ) and the nauplii of euphausiids for the Southern assemblage. This study also documented a transient coastal assemblage caused by a wind event that decreased zooplankton abundance and biomass by an order of magnitude in Fisher Strait. The zooplankton around Southampton Island reflect small-scale variability at the intersection of sub-Arctic and Arctic regions with limited estuarine influence, resulting in summer assemblages distinct from southern or western coastal Hudson Bay and nearby waters of Hudson Strait or central Hudson Bay.